KEMAMPUAN PERUSAHAAN DALAM MEMPEROLEH LABA DENGAN MODAL SENDIRI PADA PT. AQUA GOLDEN MISSISIPPI TBK - Akhmad Akhmad (Jurnal Ekonomi Trend, 2012)
This study uses a case study approach is to determine the trend of earnings, equity PT. Aqua Golden Mississippi Tbk since 2007-2009. Based on the analysis concluded that the profitability conditions Aqua Golden Mississippi Tbk getting better every year. The positive thing that memnyebabkan high number is due to an increase in thc ratio of equity financing is always followed by efficiency and increase profits. in general, the fmancial condition of the company in a stable condition and is quite good in memnghadapi future competition.